Auditory plasticity: vocal output shapes auditory cortex. - King, A (2005)
Studies in humans and songbirds have revealed a close link between vocal output and hearing. Now experiments in marmosets have shown that self-generated vocalizations can modulate the activity of neurons in the auditory cortex and even remodel their response properties.